Toxicity of naphthenic acids to invertebrates: Extracts from oil sands process-affected water versus commercial mixtures. (August 2017) - Bartlett, Adrienne J.; Frank, Richard A.; Gillis, Patricia L.; Parrott, Joanne L.; Marentette, Julie R.; Brown, Lisa R.; Hooey, Tina; Vanderveen, Ruth; McInnis, Rodney; Brunswick, Pamela; Shang, Dayue; Headley, John V.; et al.
Abstract: The toxicity of oil sands process-affected water (OSPW) has been primarily attributed to polar organic constituents, including naphthenic acid fraction components (NAFCs). Our objective was to assess the toxicity of NAFCs derived from fresh and aged OSPW, as well as commercial naphthenic acid (NA) mixtures. Exposures were conducted with three aquatic species: Hyalella azteca (freshwater amphipod), Vibrio fischeri (marine bacterium, Microtox ® assay), and Lampsilis cardium (freshwater mussel larvae (glochidia)). Commercial NAs were more toxic than NAFCs, with differences of up to 30-, 4-, and 120-fold for H. azteca, V. fischeri, and L. cardium, respectively, demonstrating that commercial NAs are not reliable surrogates for assessing the toxicity of NAFCs. Differences in toxicity between species were striking for both commercial NAs and NAFCs. Overall, V. fischeri was the least sensitive and H. azteca was the most sensitive organism. Responses of V. fischeri and H. azteca to NAFC exposures were consistent (< 2-fold difference) regardless of source and age of OSPW; however, effects on L. cardium ranged 17-fold between NAFCs. NAFCs derived from fresh OSPW sources were similarly or less toxic to those from aged OSPW. Our results support the need to better characterize the complex mixtures associated with bitumen-influenced waters, both chemically and toxicologically. Graphical abstract: Highlights: Toxicity of NAFCs derived from fresh and aged OSPW was assessed using three species. NAFCs from fresh OSPW were similarly or less toxic than those from aged OSPW. Commercial NAs were more toxic than NAFCs. Commercial NAs are not reliable surrogates to assess toxicity of NAFCs. Differences in toxicity occurred between species for both NAFCs and commercial NAs. Abstract : The toxicity of naphthenic acid mixtures varies depending on source (extracted from OSPW versus commercial mixtures), age (fresh versus aged OSPW), and species tested.